Penyusunan Laporan Keuangan Fotocopy Pamura Sesuai Dengan SAK EMKM - Putra, Yosep eka; Devi, Nayla Permata; Alhumairo, Kamila; m, Melati; Safitri, Lidia; Rahmi, Mega (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2025)
Financial reporting issues remain a major challenge for many micro and small enterprises, including Fotocopy Pamura, which initially operated without formal bookkeeping, asset records, or standardized financial statements. This study examines the preparation of financial statements for Fotocopy Pamura based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation to analyze the recording practices and reporting procedures applied in the business. The results show that the enterprise did not maintain systematic records of income, expenses, capital changes, or fixed assets, and there was no separation between the main unit and its branch. After applying SAK EMKM, the business successfully produced structured and reliable reports, including an income statement, statement of financial position, statement of cash flows, statement of changes in equity, and consolidated financial statements. The application of SAK EMKM significantly improved the relevance and reliability of financial information, enhanced transparency, and supported more accurate managerial decision-making. These findings highlight the importance of standard-based reporting for micro and small enterprises to strengthen financial accountability and business sustainability.